2017
DOI: 10.3892/ol.2017.5896
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin induces epithelial-mesenchymal transition in human breast cancer MCF-7 cells via activation of calpain

Abstract: Abstract. Fibronectin (FN) is a primary component of the mammary mesenchymal compartment and undergoes dramatic changes during breast cancer development. Increased FN expression is associated with an invasive and metastatic breast cancer phenotype. The present study demonstrated that FN causes an epithelial-mesenchymal transition (EMT)-like morphological change in MCF-7 breast cancer cells. FN stimulation caused the downregulation of epithelial markers E-cadherin and tight junction protein ZO-1, and the upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 46 publications
1
61
1
1
Order By: Relevance
“…According to the increased E-Cadherin level, a decrease of Vimentin expression, the mesenchymal marker, is measured in both tumor cells lines, especially in MDA-MB-231. Fibronectin, a mesenchymal component of mammary tissues, is reported to cause the downregulation of E-Cadherin and the EMT process in breast cancer development [38,39]. However, in our experiments we did not observe a statistical significative reduction of mesenchymal marker Fibronectin.…”
Section: Discussioncontrasting
confidence: 91%
“…According to the increased E-Cadherin level, a decrease of Vimentin expression, the mesenchymal marker, is measured in both tumor cells lines, especially in MDA-MB-231. Fibronectin, a mesenchymal component of mammary tissues, is reported to cause the downregulation of E-Cadherin and the EMT process in breast cancer development [38,39]. However, in our experiments we did not observe a statistical significative reduction of mesenchymal marker Fibronectin.…”
Section: Discussioncontrasting
confidence: 91%
“…Together, these data suggest that EGFR phosphorylation could be a stronger activator of calpain 2 than stiffness. Previous work has shown that calpain 2 has a significant correlation with an epithelial-to-mesenchymal transition [76] and lymphatic or vascular invasion, where patients with basal-like tumors and high calpain 2 expression had a significantly worse prognosis [77].…”
Section: Discussionmentioning
confidence: 98%
“…These genes, ARNTL, CCBE1, CDH13, EMP1 and FN1 have been reported as CADassociated, or related to vascular development or function [2,18,28]. In addition, they are involved in epithelial-mesenchymal transition (EMT) processes, which are prominent in vascular disease [29][30][31][32]. We validated the QTLs in CDH13 and FN1 loci with multiple approaches.…”
Section: Qtls Located In Cad Gwas Causal Loci Show Allele-specific Tcmentioning
confidence: 94%